Differences in Directors’ Remuneration and Firm Value of Malaysian Listed Firms - Mohd Waliuddin, Bin Mohd Razali; Muhammad Faizal, Abdul Manas; Janifer, Lunyai; Dyg Haszelinna, Abg Ali; Irma Yazreen, Md Yusoff (Human Resource Management Academic Research Society, 2018)
Directors’ remuneration has attracted considerable interest among scholars and financial analysts as it is seen to be one of the main reason of good firm performance. This paper aimed to examine relationship cash and non-cash director’s remuneration towards firm value in Malaysia. Data and materials were collected from Bursa Malaysia website and Eikon Thomson Reuters. Data on director’s remuneration, CEO duality and board size were obtained from the annual report whereas other variables such as the firm value, firm size and leverage were collected from Eikon Thomson Reuters database. 602 firms from different industries ranging from 2014 to 2016 period was used as the sample of this study. Regression analysis shows that non-cash directorsremuneration has a stronger significant positive relationship with firm value rather than cash remuneration. It proves that the remunerations received by directors can motivate them to perform better for the firm. The analysis also shows that board size and firm age to have a positive and significantly related with the firm value. Nonetheless, the potential limitation of using firm value as the only dependent variable may not provide more meaningful insight of the impact of other components of the performance measure such as excess in value, growth and other performance measure. Hence, future studies may use these variables for further research.